A study on self-medication in ophthalmic emergencies in the rural population of South India - Kiran Shetty; P G Vinay; Sarita R J Lobo; Lakshmi K Vijayaraghavan (Wolters Kluwer Medknow Publications, 2023)
Background: Self-medication has been defined as the taking of drugs, herbs, or home remedies on one's own initiative and advice from another person without consulting a medical specialist. The objective of the study was to identify the pattern of self-medication in ophthalmic emergencies in patients attending the emergency department in a peripheral rural setup in south India. Materials and Methods: This was a descriptive, cross-sectional, questionnaire-based observational study. The patients selected were above 18 years of age. Informed consent was taken. A questionnaire on the demographic characteristics, level of literacy, history of the ophthalmic condition for which the patient had self-medicated, type of self-medication resorted to , reasons for resorting to ocular self-medication, and the adverse effects reported were all noted in the study. Results: The study included 100 subjects. Fifty-three percent were male and 47% were female. Among the 100 subjects, 10% of the individuals were educated above primary school level. Thirty-five percent had only primary school level education and the remaining 55% had not been to a formal school and had no basic education. Among our respondents, the most commonly used self-medication was antibiotic drops (24%), followed by expired medication (23%). 20% used steroid drops. 15% had tried traditional eye medication (TEM). Herbal and other indigenous medications were used by 12% of the responders. 7% used oral nonsteroidal anti-inflammatory drug agents. None of the responders were aware of the adverse effects of self-medication. The most common ophthalmic emergency symptoms faced by our responders were excessive watering (37%), pain (28%), foreign body in the eye (14%), redness and discharge (12%), decreases vision (5%), and pain in the eye (4%). The common reasons given by our responders for not accessing health-care facilities were distance (living far from health-care facilities), advice from family and friends, belief if local healers, lack of finances and poverty, and lack of prioritizing health care. Following self-medication, 30% of the patients had infectious keratitis, 28% had conjunctivitis, 25% had epithelial defects, and 17% glaucoma. Conclusion: Irrational long-term use of drugs/traditional eye medicine or even the usage for ophthalmic emergencies can have dangerous visual outcomes. The study highlights the need of effective execution and establishment of high-quality accessible primary eye care services and health-care referral network in rural India.